T = total time
t-24/60 = driving time
d=99.5km/hr(T-24/60)
and, 66.4=d/T
so you have two equations, two unknowns: d and T
d=99.5T-99.5*24/60=66.4/T
so put that in quadratic form, and solve for T.
99.5T^2-99.5*24/60 T-66.4=0
when you get T, then solve for d
A person takes a trip, driving with a constant speed of 99.5 km/h, except for a 24.0-min rest stop. The person's average speed is 66.4 km/h.
how far does the person travel?
2 answers
oops: watch the units
(66.4km/hr) / (t hr) = 66.4/t km/hr^2
I'd say:
total distance: 99.5(t - 24/60)
avg speed = distance/time
99.5(t - 24/60)/t = 66.4
t = 1.202
distance is thus 99.5(1.202 - 24/60) = 79.8 km
(66.4km/hr) / (t hr) = 66.4/t km/hr^2
I'd say:
total distance: 99.5(t - 24/60)
avg speed = distance/time
99.5(t - 24/60)/t = 66.4
t = 1.202
distance is thus 99.5(1.202 - 24/60) = 79.8 km